Marx's concept of man - Fromm, Erich, 1900-1980 (Open Road Integrated Media, 2013)
Who was the real Karl Marx' In the Western world, and especially in the United States, Karl Marx is perceived as the spiritual godfather of Lenin and Stalin'someone bent on creating a state where everyone worships a centralized bureaucracy. Social philosopher Erich Fromm argues that Marx has been entirely misrepresented and misunderstood, and that Marx's ideas have been misappropriated to further causes antithetical to his true intentions. Fromm's study presents Marx as a humanist and social scientist. Painstakingly traveling through Marx's oeuvre, Fromm shows how Marx's real goal was to eliminate man's alienation, and allow individuals to live and appreciate a life of freedom. Furthermore, Fromm believes, Marx would have considered the Communist governments of Russia and Cuba as wrong-headed. Marx's Concept of Man also includes a selection of Marx's Early Writings, brought to English-speaking readers for the first time in 1961. This ebook features an illustrated biography of Erich Fromm, with rare images and never-before-seen documents from the author's estate.